Restoring Strength to Recycled Fibres by Blending with Kenaf Pulp - J., Latifah; Z. M. A., Ainun; I., Rushdan; S., Mahmudin (Malaysian Journal of Science, 2009)
Recycled fibres are important sources for paperboard industry in Malaysia. There are various approaches to enhance the strength of recycled fibres which include mechanical treatment, chemical addition, and physical fractionation as well as blending with virgin fibres. In this study, the old corrugated containers (OCC) pulp was subjected to blending with virgin fibres of kenaf pulp. The OCC pulp was blended with kenaf pulp at 10% interval ranging from 0 to 100% addition. Comparison was also made with OCC blended with oil palm empty fruit bunches (EFB). It was observed that blending OCC with kenaf pulp had enhanced the strength of the recycled fibres.